Bioelectrical signals improve cardiac function and modify gene expression of extracellular matrix components. (30th June 2017) - Macfelda, Karin; Kapeller, Barbara; Holly, Alexander; Podesser, Bruno K.; Losert, Udo; Brandes, Kersten; Goettel, Peter; Mueller, Johannes
Abstract: Aims: Beyond the influence of stimulating devices on cardiac excitation, their use in treating patients with heart failure has positive effects on the myocardium at the molecular level. Electrical signals can induce a wide spectrum of effects in living tissue. Therefore, we sought to determine whether applying electrical microcurrent directly to failing hearts leads to functional improvement. Methods and results: Sixteen male spontaneously hypertensive rats (SHRs) with heart failure underwent application of a patch electrode to the left ventricular epicardium and placement of a subcutaneous counter electrode. The electrode delivered a 0.35 μA microcurrent to nine of the SHRs for 45 ± 3 days; the other seven SHRs were used as controls. At baseline and before the SHRs were humanely put to death, we measured the left ventricular ejection fraction (LVEF) and the thickness of the LV posterior wall during systole and diastole (LVPWs/d). We used quantitative PCR to determine extracellular matrix parameters [collagen I–III, matrix metalloproteinase (MMP)‐2, MMP‐9, tissue inhibitor of metalloproteinases 3 (TIMP3), TIMP4, connexins (Cxs) 40/43/45, transforming growth factor (TGF)‐β, and interleukin (IL)‐6]. Among SHRs undergoing microcurrent application, LVEF normalized (mean decrease, 22.8%; P  = 0.009), and LVPWs decreased (mean, 35.3%; P  = 0.001). Compared with the control group, the SHRs receiving microcurrent exhibited a mean decrease in the gene expression of collagen I (10.6%, P  = 0.003), TIMP3 (18.5%, P  = 0.005), Cx43 (14.3%, P  = 0.003), Cx45 (12.7%, P  = 0.020), TGF‐β (13.0%, P  = 0.005), and IL‐6 (53.7%, P  = 0.000). Microcurrent application induced no changes in the expression of collagen III, MMP‐2, MMP‐9, TIMP4, or Cx40. Conclusions: Applying microcurrent to the LV epicardium of SHRs leads to statistically significant functional improvement and alterations in the levels of inflammatory and extracellular matrix components.